2010
DOI: 10.1007/s10803-009-0924-z
|View full text |Cite
|
Sign up to set email alerts
|

mRNA and Protein Levels for GABAAα4, α5, β1 and GABABR1 Receptors are Altered in Brains from Subjects with Autism

Abstract: We have shown altered expression of gamma-aminobutyric acid A (GABAA) and gamma-aminobutyric acid B (GABAB) receptors in the brains of subjects with autism. In the current study, we sought to verify our western blotting data for GABBR1 via qRT-PCR and to expand our previous work to measure mRNA and protein levels of 3 GABAA subunits previously associated with autism (GABRα4; GABRα5; GABRβ1). Three GABA receptor subunits demonstrated mRNA and protein level concordance in superior frontal cortex (GABRα4, GABRα5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
143
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(153 citation statements)
references
References 33 publications
(49 reference statements)
6
143
0
1
Order By: Relevance
“…Nearly all neuropsychiatric disorders include dysfunctional GABA system components: schizophrenia (Hashimoto et al, 2008a), bipolar disorder Guidotti et al, 2000a), anxiety (Mohler, 2012), depression (Gao et al, 2013;Thompson Ray et al, 2011), panic disorder (Malizia et al, 1998), posttraumatic stress disorder (Geuze et al, 2008), attention deficit hyperactivity disorder (Edden et al, 2012), autism (Fatemi et al, 2010(Fatemi et al, , 2002, Rett syndrome (Blue et al, 1999;Chao et al, 2010), epilepsy (Kang and Macdonald, 2009), and others (Marin, 2012). There is also some overlap in environmental risk factors such as immune system activation during development in schizophrenia and autism (Michel et al, 2012;Patterson, 2009).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Nearly all neuropsychiatric disorders include dysfunctional GABA system components: schizophrenia (Hashimoto et al, 2008a), bipolar disorder Guidotti et al, 2000a), anxiety (Mohler, 2012), depression (Gao et al, 2013;Thompson Ray et al, 2011), panic disorder (Malizia et al, 1998), posttraumatic stress disorder (Geuze et al, 2008), attention deficit hyperactivity disorder (Edden et al, 2012), autism (Fatemi et al, 2010(Fatemi et al, , 2002, Rett syndrome (Blue et al, 1999;Chao et al, 2010), epilepsy (Kang and Macdonald, 2009), and others (Marin, 2012). There is also some overlap in environmental risk factors such as immune system activation during development in schizophrenia and autism (Michel et al, 2012;Patterson, 2009).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…GABRα2, GABRβ1, GABRγ1 and GABRα4 on 4p14 (Ma et al, 2005;Vincent et al, 2006;Kakinuma et al, 2008) have also been implicated in autism. Molecular work specific to some of these GABA receptors supports their role in autism (Ma et al, 2005;Collins et al, 2006;Fatemi et al, 2010). It is also of note that GABA neurotransmission is strongly implicated in fragile X syndrome, and knockout of the fmr1 gene in mice has a hugely disruptive effect on the GABAergic system, and is a potential target for the treatment of symptoms for both Fragile-X syndrome and autism (Hagerman et al, 2005).…”
Section: Fig 3 Gabaergic Synapse In Autism and Idmentioning
confidence: 96%
“…GABRα4 was found to be involved in the etiology of autism independently and through interactions with GABRβ1 (Ma et al, 2005) and both of these genes have been linked to the autism phenotype by association (Collins et al, 2006). Recently, a study by Fatemi et al indicated that the levels of GABA receptor mRNAs in autism brains are significantly different from controls (Fatemi et al, 2010). The study shows that in the BA9 region of brains acquired from individuals with autism, levels of GABRα4, GABRα5 and GABRβ1 mRNAs are significantly decreased, while in the cerebella of these brains mRNA for these same genes are increased compared to normal controls after normalization with housekeeping genes (Fatemi et al, 2010).…”
Section: Fig 3 Gabaergic Synapse In Autism and Idmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative autoradiographic studies revealed a significant reduction in hippocampal GABA A receptors, but not in serotonin or N-methyl-D-aspartate receptors or in kainate receptors [169]. The aberrant expression of various GABA A receptor subunits has been repeatedly observed in multiple regions in brain specimens from people with ASD [170][171][172][173]. Although the precise contribution that the GABA system makes to ASD pathogenesis is inconclusive, it is likely that dysfunction in GABA signaling plays a significant role in causing the disease phenotype, and therefore requires further investigation.…”
Section: The Gamma-aminobutyric Acid Receptor Subunit Beta-3 (Gabrb3)mentioning
confidence: 99%